Gender Analysis of Sustainable Housing Choices of Rental Household Heads In Abuja Municipal Council, Nigeria - Haruna, Amos Chom; Mukiibi, Stephen; Nnaggenda-Musana, Assumpta (CSID Journal of Infrastructure Development, 2023)
Households' income and other concerns constitute important sustainable housing choices factors that play vital roles in influencing rental housing affordability decisions. The study determined both male and female households can make economic, social, and environmental housing choices to meet their affordable rental needs. A cross-sectional survey was conducted, and a questionnaire was administered to a sample of 285 households obtained from a random sampling of 450 households living in private rental housing in Trademore estate in the Lugbe district of Abuja. Among the 285 households, 226 were household heads representing 79.3% of the respondents' households. The household heads consist of 171 and 55 males and females, respectively. Data in sustainable housing choices of household heads, analyzed by principal components analysis method of exploratory factor analysis and mean rating (MR), frequencies, percentages in SPSS 25. Results indicated the sustainable economic housing choices drivers that household heads can consider for household rental affordability are Employment and Housing Prices and income and expenditure. Whereas the sustainable social housing choices drivers for household heads' rental affordability consideration were housing characteristics and access or availability of dare-care and mall, the sustainable environmental choices drivers were waste and pollution, energy efficiency, materials, and noise pollution. The study recommended that households consider the economic, social, and ecological factors for sustainable housing choices when deciding on rental accommodation to meet their rental needs. It is also advocated that both government and private investors and developers of rental housing apply the study findings to provide sustainable and affordable rentals for their clients.